2023
DOI: 10.2196/43129
|View full text |Cite
|
Sign up to set email alerts
|

The Teach-ABI Professional Development Module for Educators About Pediatric Acquired Brain Injury: Mixed Method Usability Study

Abstract: Background Acquired brain injury (ABI) is a leading cause of death and disability in children and can lead to lasting cognitive, physical, and psychosocial outcomes that affect school performance. Students with an ABI experience challenges returning to school due in part to lack of educator support and ABI awareness. A lack of knowledge and training contribute to educators feeling unprepared to support students with ABI. Teach-ABI, an online professional development module, was created to enhance e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…TeachABI is a usability tested, self-directed, online training module that provides knowledge about causes and outcomes of ABI, and strategies for educators to support elementary students with ABI in the classroom [ 21 ]. The module uses a unique case study design, sharing the narrative of a Grade 4 student who sustained an ABI at age five, and her teacher, who learns how to support her over time.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…TeachABI is a usability tested, self-directed, online training module that provides knowledge about causes and outcomes of ABI, and strategies for educators to support elementary students with ABI in the classroom [ 21 ]. The module uses a unique case study design, sharing the narrative of a Grade 4 student who sustained an ABI at age five, and her teacher, who learns how to support her over time.…”
Section: Methodsmentioning
confidence: 99%
“…TeachABI uses a case-based learning approach to discuss topics such as ABI symptoms and educational impact, and includes videos, downloadable tip sheets, and links to additional resources. A usability study by Saly et al of TeachABI reported satisfaction with the use and navigation of the module [ 21 ]. In examining task performance, >85% of participants completed 10 out of 11 module tasks independently [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations